Sistem Pengendalian Kualitas (Quality Control) Pada Proses Fabrikasi Project “Refinery Development Master Plan (RDMP)’’ - Fajri Julian; Kardiman Kardiman; Najmudin Fauji (Peneliti.net, 2022)
Fabrication is the process of processing components of raw or semi-finished materials that are assembled, shaped, and manipulated to produce new goods that have added value and function. It can also be said that fabrication is a series of jobs to build something manually or with the help of automation such as using factory tools. Quality Control or commonly abbreviated as QC which means quality control. QC can be needed in various industrial sectors, from a manufacturing to a hand production. The general task of QC is to be able to visually inspect to be able to test the product. Inspection of a product can take place before, during and after the process in production. Inspections must be carried out carefully so that any material that does not meet the standards can be rejected and maintain the quality of the material sent to the site. Finally, in working on a project, you must pay attention to other factors that can affect the course of the project so that the desired standard is maintained and progress can continue.